Evidence of Enhanced Oxygen Vacancy Defects Inducing Ferromagnetism in Multiferroic CaMn7O12 Manganite with Sintering Time - Jaiswar S.; Mandal K.D. (My University, 2025)
We provide the first experimental evidence of oxygen vacancy defect induced ferromagnetism in undoped multiferroic CaMn7O12 (CMO) manganite synthesized from the facile chemical combustion method. The obtained nanocrystalline is characterized by various techniques like TGA, FTIR, XRD, SEM-EDX, AFM, UV-visible, XPS, and SQUID, etc. to confirm the phase purity and crystallinity of CMO. Surface roughness increases with sintering time attributed to the increase of surface oxygen vacancy defects. X-ray photoelectron spectroscopy was carried out to confirm the oxidation state of constituent elements and also provides direct evidence of enhanced oxygen vacancies. UV-vis optical absorption used to infer band gap shift from 1.68 to 1.38 eV, respectively, is also attributed to increases in oxygen vacancy defects. Multiple magnetic phase transition temperatures of 90, 50, and 42 K, respectively, were obtained from the derivative of magnetization. A systematic decrease of full widths at half maxima (fwhm) of dM/dT vs T curves with sintering time indicates strengthening of ferromagnetism (FM). Transition temperature does not change significantly with sintering time, indicating the extrinsic origin of FM. The results of the UV-vis, XPS, and AFM and strengthening of ferromagnetism all are corroborated with each other's results and also attribute to enhanced oxygen vacancy concentration with sintering time. The origin of FM in undoped CMO manganite with sintering time results from bound magnetic polarons (BMPs) of enhanced iterant and the localized electron of oxygen vacancies trapped center at the surface or interfaces. Our finding also opens a new perspective for exploiting oxygen vacancy defect engineering at surfaces or interfaces in the design of exotic magnetic- and spintronics-based devices. (Graph Presented). © 2017 American Chemical Society.